Vision Based Self Localization for Humanoid Robot Soccer - Nuryono Satya Widodo; Arif Rahman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Vision based robot soccer localization system, aiming to create a robot soccer localization system. The implementation of this idea is motivated by the need of the localization system for the robot soccer to play the ball effectively and efficiently. The expected result of this research is to develop the localization system for the robot soccer based on camera vision. Thus the developed robot will be able to play football better. It is because of the localization system that can make the robot able to behave more precisely on certain condition and location. For example, the robot should be able to find the ball in its own area or in the opponent’s. Research conducted on several major parts, consisting: image capture, processing image information and directions to the information about the location of the robot at the time. The experimental results indicate that the localization system in this research work has the ability to perform an approximation of the robot location with respect to the goal.